The Defendant’s Attitude During the Main Trial and Its Impact on the Verdict: An Interdisciplinary Legal-Psychological Analysis - Ziembakowska, Aleksandra (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2025)
The correct evaluation of evidence, particularly the testimony of the accused, who plays a key role in both the pre-trial and trial stages, is an important task that the justice system is seeking to address, not only in Poland, but also internationally. An increasing number of research papers deal with the influence of psychological aspects on the distortion of judgments, such as the impact of the “halo effect” or “pure exposure”. To date, however, the impact of the defendant’s attitude on the severity of the punishment has not been systematically studied. In view of the above, this study seeks to verify the research hypothesis, which assumes that the defendant’s attitude during the main trial affects the content of the verdict, is related to the punishment imposed, and is also determined by subjective factors.